2002
DOI: 10.1074/jbc.m201895200
|View full text |Cite
|
Sign up to set email alerts
|

Tat Acetyl-acceptor Lysines Are Important for Human Immunodeficiency Virus Type-1 Replication

Abstract: The human immunodeficiency virus type-1 trans-activator Tat is a transcription factor that activates the HIV-1 promoter through binding to the trans-activationresponsive region (TAR) localized at the 5-end of all viral transcripts. We and others have recently shown that Tat is directly acetylated at lysine 28, within the activation domain, and lysine 50, in the TAR RNA binding domain, by Tat-associated histone acetyltransferases p300, p300/CBP-associating factor, and hGCN5. Here, we show that mutation of acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 59 publications
(52 reference statements)
3
49
0
Order By: Relevance
“…While P/CAF-dependent acetylation at K28 enhances the Tat transactivation potential by coordinating its interaction with cyclin T1 and the TAR RNA element (38), acetylation by p300/CBP at K50 triggers a disruption of the Tat-TAR-PTEFb complex (6,34,50). Our transactivation studies using Jurkat T cells with Tat proteins containing different lysine-toalanine point mutations demonstrated that K28A and K50A mutations also decreased the Tat C and E protein function, as described previously in the context of Tat B (4,38). Another lysine residue in the cysteine-rich domain of Tat, namely, K41, is essential for Tat function, since the mutation of this residue in Tat C and E led to a complete abrogation of Tat function, as also described previously for Tat B (43,61).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…While P/CAF-dependent acetylation at K28 enhances the Tat transactivation potential by coordinating its interaction with cyclin T1 and the TAR RNA element (38), acetylation by p300/CBP at K50 triggers a disruption of the Tat-TAR-PTEFb complex (6,34,50). Our transactivation studies using Jurkat T cells with Tat proteins containing different lysine-toalanine point mutations demonstrated that K28A and K50A mutations also decreased the Tat C and E protein function, as described previously in the context of Tat B (4,38). Another lysine residue in the cysteine-rich domain of Tat, namely, K41, is essential for Tat function, since the mutation of this residue in Tat C and E led to a complete abrogation of Tat function, as also described previously for Tat B (43,61).…”
Section: Discussionsupporting
confidence: 48%
“…Another lysine residue in the cysteine-rich domain of Tat, namely, K41, is essential for Tat function, since the mutation of this residue in Tat C and E led to a complete abrogation of Tat function, as also described previously for Tat B (43,61). This conserved residue is absolutely required for interactions with cyclin T1 (4,72) and may be important for interactions with other proteins such as P/CAF (4). The unique K40 residue of Tat E may also contribute to the interaction with cyclin T1 and to the higher affinity of Tat E for cyclin T1 than that of Tat C. As suggested before, this specific residue may also serve as a ubiquitin acceptor residue.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the sequence of the JDV chameleon has not been optimized for binding to both TARs, but it might evolve if selective pressure were simultaneously maintained for the two. Other selective influences on ARM function may occur in the context of the virus, including requirements for nuclear localization (14,24,47,48) and posttranslational modification such as Lys acetylation (7,8,16).…”
Section: Selection Of Replication-competent Hiv-1 Variants To Identifmentioning
confidence: 99%
“…Furthermore, acetylation of lysine 50 triggers the recruitment of P/CAF to the elongating RNA Pol II (Dorr, et al, 2002). P/CAF acetylates Tat on Lys28 (Kiernan, et al, 1999), which enhances the Tat-CycT1 interaction (Bres, et al, 2002). Besides acetylation other post-translational modifications appear to regulate Tat activity.…”
Section: Hiv-1 Transcription Regulationmentioning
confidence: 99%